2020
DOI: 10.1101/2020.05.17.20101915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Contributing to Healthcare Professional Burnout During the COVID-19 Pandemic: A Rapid Turnaround Global Survey

Abstract: Background: Healthcare professionals (HCPs) on the front lines against COVID-19 may face increased workload, and stress. Understanding HCPs risk for burnout is critical to supporting HCPs and maintaining the quality of healthcare during the pandemic. Methods: To assess exposure, perceptions, workload, and possible burnout of HCPs during the COVID-19 pandemic we conducted a cross-sectional survey. The main outcomes and measures were HCPs self-assessment of burnout and other experiences and attitudes associated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 15 publications
3
30
1
7
Order By: Relevance
“…Given the highly contagious nature of SARS-CoV-2, occupational hazards have been associated with more emotional impact in physicians who work on the frontline [10]. However, this study, including ICU specialists managing critically ill COVID-19 patients, did not confirm that exposure to the disease or the physical strain associated with the surge were the leading factors for symptoms of severe burnout, anxiety, and depression [10,12,13]. The number of COVID-19 patients managed, the number of night shifts per month, or time since the last vacation at the time of the surge were not associated with either symptom.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Given the highly contagious nature of SARS-CoV-2, occupational hazards have been associated with more emotional impact in physicians who work on the frontline [10]. However, this study, including ICU specialists managing critically ill COVID-19 patients, did not confirm that exposure to the disease or the physical strain associated with the surge were the leading factors for symptoms of severe burnout, anxiety, and depression [10,12,13]. The number of COVID-19 patients managed, the number of night shifts per month, or time since the last vacation at the time of the surge were not associated with either symptom.…”
Section: Discussioncontrasting
confidence: 57%
“…In a systematic review of 13 studies (33,062 participants), the pooled prevalence of anxiety and depression was 23.2%, and 22.8%, respectively [11]. In a study of healthcare providers exposed to COVID-19 patients, half of them self-perceived burnout [12]. In another study of 376 healthcare professionals in Italy, more than 1 out of 3 showed a high score of emotional exhaustion, and 1 out of 4 reported high levels of depersonalization, while around 15% reported low levels of personal accomplishment [13].…”
Section: Introductionmentioning
confidence: 99%
“…Portuguese HCWs followed the trend of burnout seen in studies from other countries [ 23 , 42 ]. Our findings show that more than half of HCWs experienced high levels of personal and work-related burnout, while most participants (64.6%) had low rates of client-related burnout.…”
Section: Discussionmentioning
confidence: 65%
“…A study conducted on healthcare professionals showed a significant positive relationship between stress and burnout (Morgantini et al, 2020). Another study investigating the relationship between burnout, anxiety, and stress disorders during the COVID-19 epidemic reported that doctors and nurses experienced high levels of mental health problems, including burnout (Sung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%